The subtalar joint complex of Australopithecus sediba. Issue 90 (January 2016) - Prang, Thomas C.
Abstract: The hominin talus has figured prominently in previous studies of the functional morphology of the talocrural joint, but the talocalcaneal and talonavicular joints have received comparatively less attention despite their functional importance as components of the subtalar joint complex. An associated complete talus and calcaneus attributed to the Malapa Hominin 2 (MH2) individual of Australopithecus sediba offers the opportunity to evaluate the subtalar joint complex in an early hominin. Furthermore, detailed morphological comparisons of A. sediba to other fossil hominins such as Australopithecus africanus have not yet been conducted. Here I quantify joint curvatures and angular measurements among extant hominoids and fossil hominins to evaluate the functional morphology of the subtalar joint complex of A. sediba . Australopithecus sediba uniquely combines talocalcaneal joint morphology indicative of mobility with specializations of the talonavicular joint that provide medial midtarsal stabilization. Multivariate analyses of talus and calcaneus variables show that A. sediba is most similar to extant gorillas in the morphology of the subtalar joint complex. In contrast, other hominins, such as OH 8, are more similar to modern humans. The morphological similarity between MH2 (U.W. 88-98/99) and specimens from Sterkfontein, Member 4 (StW 88, StW 102, StW 352) in morphologies of the talonavicular and talocalcaneal joints suggests that A. sediba may have possessed a foot that was functionally similar to that of A. africanus . This combination of morphologies in the A. sediba foot is probably derived among hominins and suggests that arboreality may have been adaptively significant for southern African Australopithecus .